Spray coverage and deposits from a remotely piloted aerial application system using various nozzle types - Butts, Thomas R.; Fritz, Bradley K.; Davis, Jason A.; Spurlock, Terry N. (Frontiers in Agronomy, 2024)
Remotely piloted aerial application systems (RPAAS) are exponentially increasing globally for pesticide applications. Evaluations of spray coverage, deposits, and droplet size, when implementing various application parameters, are needed to optimize these applications. A RPAAS at 46.8 L ha-1 provided similar or greater coverage and deposits to ground equipment at 93.5 L ha-1 across nozzle types evaluated excluding the XR. The RPAAS at 18.7 L ha-1 had reduced coverage (<9% total coverage) and deposits (<350 total deposits cm-2) regardless of nozzle type evaluated compared to the other two application setups. The top and back WSP locations had considerably greater coverage and deposits than the front WSP location likely due to wind speed and direction being more important drivers for spray dynamics than direction of sprayer travel. Generally, nozzle selection was less critical for coverage and deposits from RPAAS at 18.7 L ha-1. The AITTJ60, AIXR, and TADF nozzle types may be optimum options for RPAAS, particularly at 46.8 L ha-1, as they improved coverage, deposits, and estimated recovery rate while producing the greatest droplet size, thereby reducing spray drift potential. Results of this research demonstrated coverage, deposits, and droplet size from RPAAS at 46.8 L ha-1 can be equivalent to ground spray equipment at 93.5 L ha-1 across a range of nozzle types and therefore, may be viable for effective pesticide applications. Applications using RPAAS at 18.7 L ha-1 resulted in considerably less coverage and deposits across nozzle types evaluated, and would be at risk for reduced pesticide efficacy.